Maternal mortality - Pacheco Romero, José (2015)
It is a retrospective study of 65 cases of maternal death that occurred in the National Hospital Edgardo Rebagliati Martins (1971-1980), representing a rate of 4.0 per 10,000 live births. 63% of the mothers were 20-34 years and 37% were older than 35 years. 21% were primiparous and 17% had more than five pregnancies. 33% were full-term and 30% were less than 20 weeks pregnant. Among the causes of hospitalization they excelled: hypertensive disease 26%, febrile syndrome, abortion, premature rupture of membranes, heart failure, labor and puerperal endometritis. They were important antecedents: I abortion 24%, previous cesareans, urinary infection, heart disease, tuberculosis, stillbirths. Obstetric causes of death were infections 26% (including postpartum endometritis, infected abortion, chorioamnionitis), hipertensica disease 26%, 6% and bleeding. Among the non-obstetric causes: cardiovascular 11%, usually infectious process, acute liver disease lung disease. Possibly 40% of deaths and could forestall. 24% of women died within 24 hours of admission to hospital and 43% within 48 hours. The results are very satisfactory, but improved with a more comprehensive prenatal care, the creation of the High Risk Unit, uniform criteria for the management of pregnant women and a better implementation.